Efficiency and Enhancement in Attention Networks of Elite Shooting and Archery Athletes - Lu, Quanyu; Li, Pengli; Wu, Qiong; Liu, Xinghua; Wu, Yanhong (Frontiers in Psychology, 2021)
Attention has been theorized as a system comprising three networks that can be estimated reliably by the attention network test (ANT); the three networks are defined as alerting, orienting, and conflict control. The present study aims to identify the attention networks that are crucial for elite shooting and archery athletes and to examine whether mindfulness training can improve elite athletes' attention networks. We compared the performances in ANT between 62 elite athletes (27 F/35 M, 23.66 ± 4.95 years) from the Chinese national team of shooting and archery and 49 athletes (19 F/30 M, 19.53 ± 3.38 years) from a provincial team in China. The results indicate three well-functioned attention networks in both groups, but elite athletes in the national team responded faster overall than athletes in the provincial team (Diff = 28.84 ms, p = 0.006). The 62 elite athletes in the national team then received mindfulness training with varied periods ranging from 5 to 8 weeks, after which the ANT was re-administered. After mindfulness training, the elite athletes improved in orienting (Diffspatial = 10.02 ms, p = 0.018) and conflict control networks (Diffincon = 12.01 ms, p = 0.019) compared with their pre-training performances. These results suggest that elite shooting and archery athletes in the national team are more efficient in all three attention networks, which means that they are able to reach the alerting state faster, make better use of environmental information, and suppress interference from distractors more efficiently. Moreover, the orienting and conflict control networks of the elite shooting and archery athletes can be improved by mindfulness training. We conclude that mindfulness practice should be considered as a useful addition to daily training for shooting and archery athletes.